2008
DOI: 10.1001/archsurg.143.8.756
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Results of Subtotal vs Total Parathyroidectomy Without Autotransplantation in Kidney Transplant Recipients

Abstract: Total parathyroidectomy without autotransplantation in kidney transplant recipients leads to reduced recurrence rates and similar improvement of clinical symptoms compared with subtotal parathyroidectomy.Design: A retrospective cohort study.Setting: University clinic.Patients: Thirty-three patients with functioning renal grafts who underwent primary total (n = 17; group 1) or subtotal (n = 16; group 2) parathyroidectomy for renal hyperparathyroidism.Main Outcome Measures: Long-term levels of intact parathyroid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 20 publications
3
34
0
3
Order By: Relevance
“…The correlation between pain and calcium showed a weak positive correlation, which is in concordance with a study by Rayes et al [63], who found a reduction of bone pain when calcium levels dropped to the normal range. A positive correlation between bone pain and osteocalcin was described in a long-term study by Hampl et al [64], where an increased physical activity and endurance was interpreted as a reduction of bone pain.…”
Section: Discussionsupporting
confidence: 91%
“…The correlation between pain and calcium showed a weak positive correlation, which is in concordance with a study by Rayes et al [63], who found a reduction of bone pain when calcium levels dropped to the normal range. A positive correlation between bone pain and osteocalcin was described in a long-term study by Hampl et al [64], where an increased physical activity and endurance was interpreted as a reduction of bone pain.…”
Section: Discussionsupporting
confidence: 91%
“…It is also well worth noting that all recurrences occurred in patients who were receiving dialysis treatment (26,27). Therefore, the most important reason for recurrence was related not to the surgical approach itself but rather to the effects of longstanding renal disease, given that no recurrence was observed among patients who received renal transplantation, even throughout a long follow-up period.…”
Section: Discussionmentioning
confidence: 99%
“…Until very recently, the recommended surgical procedure for patients with HPT after renal transplantation was similar to that for patients with renal HPT under dialysis, a form of subtotal resection of all parathyroid tissue (usually subtotal PTX or total PTX+AT), because of the increased risk of recurrence if more parathyroid tissue is left in place [34,116] However, despite recent reports suggesting that hypoparathyroidism, even if definitive, is manageable in patients with a good renal function [66,[137][138][139], it seems that the current trend is to be less aggressive for three main reasons:…”
Section: Extent Of Surgery In Persistent Hpt After Renal Transplantationmentioning
confidence: 99%